Penerapan Algoritma Dijkstra pada Pendistribusian Bahan Bakar Minyak di Pontianak - Riski Apriadi; Bayu Prihandono; Yundari Yundari (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2023)
Determination of the shortest path or the fastest travel time is a problem that occurs to drivers of trucks loaded with fuel oil (BBM) when delivering their tanks to one of the public refueling stations (SPBU) in Pal Lima. To get to the destination, several paths that can be passed. This study aims to determine the shortest path and fastest travel time using Dijkstra's algorithm. Dijkstra's algorithm can be used on both directed and weighted graphs. The first step that must be done is to determine the starting node and destination node. After that, the calculation is carried out from the initial departure node to the neighboring node, the node with the smallest weight is used as the next calculation node. The same is done until all nodes are evaluated. Crossroads are assumed as vertices and between intersections as edges in Dijkstra's algorithm. From the results of the study, the shortest path was obtained through the Kapuas 2 Toll Road, Jl. Adi Sucipto, Jl. Imam Bonjol, Jl. Tanjung Pura, Jl. Rahadi, Jl. Mr. Love, Jl. Hassanudin, Jl. H. Rais, Pal III, Pal V with a minimum distance of 12,768 Km. For the fastest route, it is through the Kapuas 2 Toll Road, Jl. Major Alianyang, Jl. Arteri Supadio, Jl. General Ayani, Jl. Abdurrahman, Jl. Sultan Syahrir, Dr. Sutomo, Jl. Dr. Wahidin, Jl. Pal V with the fastest travel time of 27 minutes.